POLA SINTAKSIS DAN PILIHAN KATA DALAM UMPAMA DAN UMPASA - RAHIMAH, ANNI (JURNAL EDUCATION AND DEVELOPMENT, 2017)
This study aims to describing the syntax form and diction of Umpama and Umpasa. Umpama is a proverb and Umpasa is a âpantunâ in Batak. The conclusion from this study can be concluded that the syntax form contained in the base is generally classified as a subordinate clause form. Subordinate clause has an incomplete structure. The elements contained in the clause can be either predicate or adjunct. Subordinate clause is incapable of being a major sentence. Subordinate clause can be known from the conjunction or correlation between clause, frase and sentence contained in front of it as in the set, while the types of diction in this study contains about the diction of affirmation, diction of denotative, diction of conotative and diction of synonym.